INOVASI MEDIA PEMBELAJARAN SEBAGAI STRATEGI ADAPTIF TERHADAP KARAKTERISTIK BELAJAR GENERASI Z DI ERA DIGITAL - Sofiana Sholikah; Sinta Titis Pangesti Putri Ciptami; Muhammad Zaini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Technological advancements in the digital age have had a significant impact on the learning patterns of Generation Z, who tend to prefer interactive, creative, and technology-based learning. This situation underscores the need for innovative learning media that are adaptive and relevant to the times. This study employs a descriptive qualitative approach using library research. Data were collected from books, scientific journals, academic articles, and previous studies, which were analyzed using content analysis. This study aims to explain the concept of innovative learning media in the digital age, the learning characteristics of Generation Z, learning innovations that are adapted to the learning characteristics of Generation Z, as well as the opportunities and challenges of implementing innovative learning media in the digital age. The results of this study indicate that innovative learning media play a crucial role in enhancing the quality of learning interactions. The learning characteristics of Generation Z include a preference for visual and audiovisual learning resources, self-directed learning, a need for rapid feedback, a shorter attention span, prominent collaboration and creativity in the learning process, a strong awareness of practical relevance, and a tendency toward social learning. Adaptive strategies that can be implemented include integrating digital media into learning, tailoring instructional materials to Generation Z's learning needs, applying active and reflective learning models, integrating character values and digital literacy, and optimizing the teacher's role as an innovator and instructional material developer. The challenges and opportunities for implementation include infrastructure and internet access, teacher training and readiness, data security and privacy, accessibility and inclusivity, personalization and differentiation, and global collaboration. Keywords: Learning Media Innovation, Generation Z Learning Characteristics, Digital Age